Advances in Bioinformatics and Computational Biology 6th Brazilian Symposium on Bioinformatics, BSB 2011, Brasilia, Brazil, August 10-12, 2011. Proceedings - Norberto de Souza, Osmar; Telles, Guilherme P.; Palakal, Mathew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 6th Brazilian Symposium on Bioinformatics, BSB 2011, held in Brasília, Brazil, in August 2011. The 8 full papers and 4 extended abstracts presented were carefully peer-reviewed and selected for inclusion in this book. The BSB topics of interest cover many areas of bioinformatics that range from theoretical aspects of problems in bioinformatics to applications in molecular biology, biochemistry, genetics, and associated subjects.
Keywords: Computer science; Computer software; Database management; Artificial intelligence; Optical pattern recognition; Bioinformatics; Computer Science; Artificial Intelligence (incl. Robotics).; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Database Management; Computational Biology/Bioinformatics.; Pattern Recognition